2010
DOI: 10.2215/cjn.03980510
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Mood, Usual Activity Level, and Continued Employment after Starting Dialysis

Abstract: Background and objectives: When patients start dialysis, their employment rate declines and disability benefits are an option. With patient sociodemographic and clinical characteristics including disability income status controlled, we investigated the significance of depressed mood and usual activity level as predictors of patients' continued employment after dialysis start.Design, setting, participants, & measurements: Incident patients from 296 randomly selected dialysis clinics were surveyed in the Compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 26 publications
2
56
0
10
Order By: Relevance
“…Many possible factors infusing employment status were reported such as age, gender, education levels, lifestyle, dialysis modality, medical insurance, serum albumin, anemia, physical and psychological functioning, disease etiology(diabetes), availability of late-shift dialysis, training, and high-frequency hemodialysis [9,10,[17][18][19][20][21]. However, in our study, we observed that only increasing age, lower educational level, and higher annual income were identified as independent risk factors for loss of employment.…”
Section: Discussionmentioning
confidence: 99%
“…Many possible factors infusing employment status were reported such as age, gender, education levels, lifestyle, dialysis modality, medical insurance, serum albumin, anemia, physical and psychological functioning, disease etiology(diabetes), availability of late-shift dialysis, training, and high-frequency hemodialysis [9,10,[17][18][19][20][21]. However, in our study, we observed that only increasing age, lower educational level, and higher annual income were identified as independent risk factors for loss of employment.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between decline of energy level and maintenance of employment after dialysis initiation has been observed [16]. Indeed, Kutner et al [17] reported that patients who remained employed had a lower score on the Patient Health Questionnaire 2 (PHQ-2) depression measure; on the basis of The rounded rectangles denote the categories generated from concepts by a grounded theory approach, and the ovals designate our interpretations the PHQ-2 cutoff score ≥3, 12.1% of the 191 patients who remained employed had possible or probable depression, compared with 32.8% of the 394 patients who were no longer employed.…”
Section: Discussionmentioning
confidence: 98%
“…Our results also suggest that resignation from paid work further continues in the dialysis phase. Findings from a study conducted by Kutner et al (2010) also point to job resignation during the pre-dialysis phase and the initiation phase of dialysis treatment. Their study showed that, among 585 incident patients who were working for pay during the year before dialysis, only 191 (32.6%) continued working approximately 4 months after dialysis start.…”
Section: Introductionmentioning
confidence: 99%
“…However, patient-level characteristics were not taken into account, and due to the design of the study the associations observed between facility characteristics and patient employment could not be interpreted as cause-and-effect relationships. Another study by Kutner et al (2010) revealed that higher levels of energy expenditure reflected in usual activity levels were associated with increased likelihood of continued employment after dialysis start. The labour participation rate of 24% found in our study among Dutch dialysis patients of working age is considerably lower than that of the general Dutch population in the ages of 15-64 years, of which 65% were employed for at least 12 hours per week in 2006.…”
Section: Introductionmentioning
confidence: 99%